Photo-induced instability of nanocrystalline silicon TFTs - Bauza, Marius (2011)
We examine the instability behavior of nanocrystalline silicon (nc-Si) thin-film transistors (TFTs) in the presence of electrical and optical stress. The change in threshold voltage and sub-threshold slope is more significant under combined bias-and-light stress when compared to bias stress alone. The threshold voltage shift (Delta V-T) after 6 h of bias stress is about 7 times larger in the case with illumination than in the dark. Under bias stress alone, the primary instability mechanism is charge trapping at the semiconductor/insulator interface. In contrast, under combined bias-and-light stress, the prevailing mechanism appears to be the creation of defect states in the channel, and believed to take place in the amorphous phase, where the increase in the electron density induced by electrical bias enhances the non-radiative recombination of photo-excited electron-hole pairs. The results reported here are consistent with observations of photo-induced efficiency degradation in solar cells.